Hepcidin Is Down-Regulated in Alcohol Loading - Ohtake, Takaaki; Saito, Hiroyuki; Hosoki, Yayoi; Inoue, Mitsutaka; Miyoshi, Shigeki; Suzuki, Yasuaki; Fujimoto, Yoshinori; Kohgo, Yutaka (Alcoholism, clinical and experimental research, 2007)
Background: It is common for alcoholic patients to have excess iron accumulation in the liver, which may contribute to the development of alcoholic liver disease (ALD). However, the mechanism of hepatic iron uptake in ALD is still obscure. Recently, a novel iron‐regulatory hormone hepcidin was found that suppresses the absorption of iron from the small intestine and the release of iron from macrophages. To elucidate the contribution of hepcidin toward the hepatic excess iron accumulation in ALD, we examined whether alcohol loading affects hepcidin expression both in ALD patients and in an ethanol‐fed mouse model. Methods: Serum prohepcidin concentration was quantified by enzyme‐linked immunosorbent assay. Hepatic hepcidin‐1 and hepcidin‐2 mRNA expressions in mouse liver were evaluated by quantitative real‐time reverse‐transcriptase polymerase chain reaction method. The protein expression of prohepcidin in mouse liver was examined immunohistochemically by rabbit antimouse prohepcidin antibody. Results: Serum prohepcidin concentration in ALD was significantly lower than that in healthy subjects (p<0.001). Especially, serum prohepcidin concentrations were decreased in the patients whose serum ferritin value was high. In the ethanol‐fed mouse model, hepatic hepcidin‐1 mRNA expression was significantly lower than that in control (p=0.04). Prohepcidin was expressed in the cytoplasm of hepatocytes of mice liver tissue sections, and its expression was decreased after ethanol loading. Conclusion: Alcohol loading down‐regulates hepatic hepcidin expression and leads to the increase of iron absorption from the intestine.